ANALYSIS ON DETERMINATION OF LEAKAGE FLOW AND SEPARATION FORCE OF GAS TURBINE ENGINE - G. Shantha G. Sudha (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Determination of leakage flow and separation force of gas turbine engine mainly seals and similar devices represents a cinque application of the qziasi-one-dimensional compressible.flow equation. This nonlinear equation has been solved numerically by varioztszithers’, for nozzle, diffuser, duct, seal, and similar applications. It has been found, however, that the solitonmalteds reported in tile literature may be inoperative for seals wit11 small clearance to-length ratio, or when the seal is appreciably distorted. This deficit is cawed by a bindery layer type behaviourresulting, from a singularity in twovicinities of sonic flow, i.e., when the flow Mach number approaches unity. This new analysis considers the combined effects of entrance losses, fluid inertia, fluid,friction, area change, and,fluid turbulence and is applicable to steady, one dimensional gas,/2ow in general. The compacter program acetylates the distribution of pressure, temperature, velocity, Mach cumber, and Reynolds cycleralong the flow path.